2020
DOI: 10.1186/s12935-020-01302-y
|View full text |Cite
|
Sign up to set email alerts
|

Serum-derived three-circRNA signature as a diagnostic biomarker for hepatocellular carcinoma

Abstract: Background: Hepatocellular carcinoma (HCC) is a common tumor characterized by high morbidity and mortality rates. The importance of circRNA in cancer diagnosis has been established. The study aimed to identify differentiallyexpressed circRNAs (DECs) in human blood exosomes from patients with HCC and to investigate their diagnostic value. Methods: The circRNA expression profiles of HCC and normal human blood samples were downloaded and processed from the exoRBase database. At the cutoff criteria of a fold chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 26 publications
0
52
0
Order By: Relevance
“…Despite this study being performed in whole serum RNA extracts, consistency was found with the data retrieved from the exoRBase database [109] (http://www.exorbase.org/exoRBase/toIndex), which include exosomal circRNAs from 21 HCC patients. Indeed, the diagnostic potential of these three candidates was also verified through ROC curve analysis, showing the discriminatory potential of the circRNAs between HCC patients and controls with an AUC always above 0.70 [65].…”
Section: Free-circulating Circrnasmentioning
confidence: 88%
“…Despite this study being performed in whole serum RNA extracts, consistency was found with the data retrieved from the exoRBase database [109] (http://www.exorbase.org/exoRBase/toIndex), which include exosomal circRNAs from 21 HCC patients. Indeed, the diagnostic potential of these three candidates was also verified through ROC curve analysis, showing the discriminatory potential of the circRNAs between HCC patients and controls with an AUC always above 0.70 [65].…”
Section: Free-circulating Circrnasmentioning
confidence: 88%
“…Sun et al. ( 81 ) report that hsa_circ_0004001, hsa_circ_0004123 and hsa_circ_0075792 are upregulated in the blood samples of HCC. ROC analysis shows that the AUC value of the combination of the three circRNAs is 0.89, indicating that the combination of the three circRNAs could be a potential diagnostic biomarker in HCC.…”
Section: Clinical Significance Of Circrna In Hccmentioning
confidence: 99%
“…By analyzing differentially expressed circRNAs (DECs) in plasma between 40 healthy controls and 71 HCC patients, Sun et al recently identified a three-circRNA signature, including hsa_circ_0004001, hsa_circ_0004123, and hsa_circ_0075792, which are highly expressed in HCC patients (50). This 3-circRNA signature showed a potent diagnosis value (AUC: 0.89, sensitivity: 0.905; specificity: 0.781) (50).…”
Section: Circrnas As Non-invasive Diagnosis Biomarkers Of Hccsmentioning
confidence: 99%
“…By analyzing differentially expressed circRNAs (DECs) in plasma between 40 healthy controls and 71 HCC patients, Sun et al recently identified a three-circRNA signature, including hsa_circ_0004001, hsa_circ_0004123, and hsa_circ_0075792, which are highly expressed in HCC patients (50). This 3-circRNA signature showed a potent diagnosis value (AUC: 0.89, sensitivity: 0.905; specificity: 0.781) (50). In this study, the authors did not compared the diagnosis value of the 3-circRNA signature with that of AFP, but the AUC, sensitivity and specificity values of the 3-circRNA signature may slightly better than those of AFP from other studies (48,49).…”
Section: Circrnas As Non-invasive Diagnosis Biomarkers Of Hccsmentioning
confidence: 99%